Lunar-sea-imitated basalt glass fiber and preparation method thereof
By simulating the lunar soil components and optimizing the raw material components, imitating lunar sea basalt glass fibers with high elastic modulus and good process performance were prepared, which solved the problems of low elastic modulus and poor process performance of existing basalt glass fibers, and achieved the goal of preparing using lunar resources.
Patent Information
- Application Number
- CN202411908170.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-25
AI Technical Summary
The existing basalt glass fibers have low elastic modulus, poor process performance and cannot be prepared using lunar resources.
By collecting component data of lunar soil in different regions of the moon, using chemical raw materials to physically simulate lunar soil components, optimizing the content of each raw material component, and preparing imitation lunar sea basalt glass fibers.
The elastic modulus and process performance of basalt glass fibers are improved, and basalt glass fibers are prepared by using only lunar soil components under low gravity conditions.
Smart Images

Figure BDA0005204914370000091 
Figure BDA0005204914370000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of basalt glass fiber preparation, and in particular to a mare-like basalt glass fiber and a preparation method thereof. Background Art
[0002] Basalt continuous fiber is made of natural basalt ore as raw material. It is drawn at high speed through a platinum-rhodium alloy drawing plate after high-temperature melting. It has the characteristics of high strength and high elastic modulus. It also has excellent properties such as high temperature resistance, low temperature resistance, acid and alkali resistance, oxidation resistance, radiation resistance, thermal insulation and sound insulation, fire retardant, good filterability, high compression strength and shear strength. It is one of the four high-performance fibers that my country focuses on developing.
[0003] Compared with other high-tech fibers, basalt fiber is very different, especially in terms of raw materials. The basalt ore used to produce basalt fiber is a natural ore, composed of oxides such as SiO2, TiO2, Al2O3, FeO, Fe2O3, MnO, MgO, CaO, K2O, Na2O, P2O5 and other trace elements, with a complex composition. However, existing basalt fiber products still have problems such as low elastic modulus and poor process performance; at the same time, existing basalt fibers are often prepared from natural ores on Earth, and the components in the lunar soil are quite different from the ore, so it is impossible to use lunar resources to prepare basalt glass fibers.
[0004] Based on this, there is an urgent need to provide a mare imitation basalt glass fiber and a preparation method thereof. Summary of the invention
[0005] The embodiment of the present invention provides a lunar-sea basalt-like glass fiber and a preparation method thereof, which can solve the problems that traditional basalt glass fibers have a low elastic modulus, poor process performance, and cannot be prepared using lunar resources.
[0006] In a first aspect, the present invention provides a mare-like basalt glass fiber, wherein the raw material for preparing the mare-like basalt glass fiber is determined based on lunar soil component data;
[0007] The raw materials include the following components in percentage by mass: SiO2: 42-50%, Al2O3: 12-18%, MgO: 7-12%, CaO: 10-14%, FeO: 8-20%, MnO: 0.05-0.4%, TiO2: 1-8%, P2O5: 0.05-0.5%, Cr2O3: 0.05-0.4%.
[0008] Preferably, in terms of mass percentage, it further comprises: Na2O: 0-0.3%, K2O: 0-0.3%.
[0009] Preferably, the sum of the mass percentages of SiO2, Al2O3, CaO and MgO is not less than 75%.
[0010] Preferably, the sum of the mass percentages of CaO and MgO is not less than 18%.
[0011] Preferably, the ratio of the sum of the mass percentages of SiO2 and Al2O3 to the sum of the mass percentages of CaO and MgO is not less than 2.8.
[0012] Preferably, the mass percentage of FeO is 10-18%.
[0013] Preferably, the prepared raw materials include the following components, in mass percentage: SiO2: 42-47%, Al2O3: 13-16%, MgO: 8.5-12%, CaO: 10-12.5%, FeO: 9.5-17%, MnO: 0.2-0.4%, TiO2: 1-7%, P2O5: 0.1-0.4%, Cr2O3: 0.1-0.35%.
[0014] In a second aspect, the present invention provides a method for preparing the imitation mare basalt glass fiber according to any one of the first aspects above, the preparation method comprising the following steps:
[0015] (1) Conducting phase analysis on lunar soil samples collected from several regions to determine the composition of the lunar soil samples;
[0016] (2) According to the components of the lunar soil samples, the composition of basalt glass fiber was determined and the content of each component was optimized to obtain the raw materials of lunar mare basalt glass fiber;
[0017] (3) melting the constituent raw materials of the imitation mare basalt glass fiber to obtain homogeneous glass;
[0018] (4) Drawing the homogeneous glass to obtain the imitation mare basalt glass fiber.
[0019] Preferably, the diameter of the simulated mare basalt glass fiber is 8-22 μm, and the elastic modulus is greater than 90 GPa.
[0020] In a third aspect, the present invention provides a use of the imitation mare basalt glass fiber described in any one of the first aspects in a composite material reinforcement.
[0021] Compared with the prior art, the present invention has at least the following beneficial effects:
[0022] In the present invention, by collecting the component data of lunar soil in different regions of the moon, chemical raw materials are used to perform physical simulation on the lunar soil components in different regions, and based on the lunar soil component data in different regions and the performance of basalt glass fiber, the selected raw material components are regulated. On the one hand, the processability of basalt glass fiber is improved, and the basalt glass formed by the above component content has good uniformity during melting and can achieve stable wire drawing production. On the other hand, not only the elastic modulus of basalt glass fiber is improved, but also the preparation of basalt glass fiber can be achieved under low gravity conditions using only lunar soil components. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] The construction of a lunar base is the initial mission goal of human exploration of the moon and outer space. However, the cost of transportation between the earth and the moon is high. In the future, the construction of a lunar base is likely to adopt the method of "taking local materials", that is, directly using lunar resources. Lunar soil is a resource that can be taken everywhere on the surface of the moon. If it can be used effectively, it will inevitably greatly reduce the construction cost of the base. Therefore, using existing chemical raw materials to simulate lunar soil can not only make up for the shortage of real lunar soil samples, expand the scope and depth of lunar scientific research, reduce the consumption and dependence on real lunar soil samples, but also realize the effective use of lunar soil resources.
[0025] Therefore, the embodiment of the present invention collects the composition data of lunar soil from different regions of the moon, and on this basis uses chemical raw materials to physically simulate the composition of lunar soil from different regions, and further prepares lunar sea basalt fiber by using chemical raw materials to simulate the lunar soil components from different regions for the purpose of enhancing the elastic modulus and process performance of basalt fiber, thereby providing a basalt glass fiber that can be prepared in a lunar environment.
[0026] The embodiment of the present invention provides a mare-like basalt glass fiber, wherein the raw material for preparing the mare-like basalt glass fiber is determined based on lunar soil component data;
[0027] In terms of mass percentage, the raw materials for preparation include the following components: SiO2: 42-50% (for example, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% or 50%), Al2O3: 12-18% (for example, 12%, 13%, 14%, 15%, 16%, 17% or 18%), MgO: 7-12% (for example, 7%, 8%, 9%, 10%, 11% or 12%), CaO: 10-14% (for example, 10%, 11%, 12%, 13% or 14%), FeO: 8-20% (for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%), MnO: 0.05-0.4% (for example, it can be 0.05%, 0.08%, 0.1%, 0.2%, 0.3% or 0.4%), TiO2: 1-8% (for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%), P2O5: 0.05-0.5% (for example, it can be 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4% or 0.5%), Cr2O3: 0.05-0.4% (for example, it can be 0.05%, 0.08%, 0.1%, 0.2%, 0.3% or 0.4%).
[0028] In the embodiment of the present invention, by collecting the composition data of lunar soil from different regions of the moon, chemical raw materials are used to perform physical simulation of the lunar soil components in different regions, and based on the lunar soil composition data of different regions and the performance of basalt glass fiber, the selected raw material components are regulated. On the one hand, the processability of the basalt glass fiber is improved, and the basalt glass formed by the above-mentioned component content has good uniformity during melting and can achieve stable wire drawing production. On the other hand, not only the elastic modulus of the basalt glass fiber is improved, but also the basalt glass fiber can be prepared under low gravity conditions using only the lunar soil component.
[0029] In the embodiment of the present invention, by analyzing the components of lunar soil in different regions, it is found that SiO2 accounts for a high proportion of lunar rocks in the lunar soil, and SiO2 can be used as a network former of glass fiber structure, and its irregular continuous network structure composed of silicon-oxygen tetrahedrons can enhance the mechanical strength of glass fiber, and the structure has a high bond strength, a tight structure, and is not easy to polarize under the action of an external electric field, nor is it easy to produce losses such as conductivity and relaxation, so a high content of SiO2 can also significantly reduce the dielectric constant and dielectric loss of glass fiber. However, if the SiO2 content is too high, the viscosity of the melted glass will be too large, making it difficult to melt, and the glass melt will easily produce crystallization, which is not conducive to the forming of glass fiber. Therefore, in the embodiment of the present invention, the SiO2 content range is limited to 42%-50%.
[0030] Al2O3 exists as an intermediate in the glass fiber structure and enters the glass network structure as [AlO4] tetrahedron, which can not only enhance the density of the glass fiber network structure and reduce the phase separation tendency of the glass, but also inhibit the formation of crystal nuclei to improve the process performance of the glass fiber. At the same time, it is beneficial to improve the elastic modulus and chemical corrosion resistance of the glass fiber. With the increase of Al2O3 content, the elastic modulus of the glass fiber gradually increases. However, when the amount introduced is too high, a large number of network exosomes will appear, making the glass melting temperature too high and the crystallization tendency enhanced. Therefore, the mass percentage of Al2O3 suitable in the embodiment of the present invention is 12-18%.
[0031] MgO and CaO are both external bodies of the glass network structure. MgO mainly provides free oxygen in the glass components to promote the formation of tetrahedral structures in the intermediates to enhance the network density of the glass, while reducing the high-temperature viscosity of the glass and improving the tendency of crystallization, thereby improving the mechanical properties and forming process performance of the glass. MgO has a small radius, high charge, and strong polarization ability. MgO can accumulate and increase the degree of polymerization of the glass network, thereby improving the elastic modulus of the glass. In addition, increasing the MgO content can make some Mg 2+ It exists in the form of [MgO4] tetrahedron and forms a glass structure skeleton with [SiO4] tetrahedron, thereby reducing the density of glass fiber and significantly improving the elastic modulus of glass fiber. However, excessive MgO content will increase the viscosity of the glass and cause crystallization. Therefore, in the embodiment of the present invention, the content of MgO is 7-12%.
[0032] Considering that most of the iron in the lunar soil exists in the form of FeO, a relatively high content of FeO is added in the embodiment of the present invention. FeO plays a key role in the process performance of basalt glass and can give basalt fiber a certain metallic luster. An appropriate content of FeO can ensure that the glass does not precipitate crystals and has good wire drawing performance. However, if the content of FeO is too high, the glass will easily undergo phase separation, thereby reducing the process performance of the glass. Therefore, in the embodiment of the present invention, FeO is limited to 8-20%.
[0033] TiO2 is also a network exosome in the glass structure. TiO2 can improve the glass forming property and chemical durability. The present invention has experimentally confirmed that a small amount of TiO2 can reduce the high temperature viscosity of glass and improve the acid resistance of glass fiber, but too high a TiO2 content will make the glass easy to phase separate. Therefore, the suitable TiO2 mass percentage in the embodiment of the present invention is 1-8%.
[0034] MnO, Cr2O3 and P2O5 are characteristic elements in the present invention, wherein MnO mainly acts as a glass network former and is filled in the network structure of the glass, thereby improving the compactness of the glass network, while improving the glass stability, the modulus and the mechanical strength of the glass; P2O5 is one of the glass network formers, which helps to reduce the number of non-bridging oxygens in silicate glass and aggregate the network structure; by cooperating with SiO2 and Al2O3, it can further enhance the mechanical properties of the glass fiber; the addition of Cr2O3 can improve the elastic modulus and sintering resistance of the glass fiber.
[0035] According to some preferred embodiments, the following components are further included, in terms of mass percentage: Na2O: 0-0.3% (0.1%, 0.2% or 0.3%), K2O: 0-0.3% (for example, 0.1%, 0.2% or 0.3%).
[0036] The above-mentioned impurities are inevitably introduced in the embodiments of the present invention. By controlling the content of the impurity components to not exceed 0.3% at most, the influence of the impurity components on the performance of the basalt glass fiber can be avoided.
[0037] According to some preferred embodiments, the sum of the mass percentages of SiO2, Al2O3, CaO and MgO is not less than 75%.
[0038] According to some preferred embodiments, the ratio of the sum of the mass percentages of SiO2 and Al2O3 to the sum of the mass percentages of CaO and MgO is not less than 2.8.
[0039] SiO2 can form an irregular continuous network with silicon oxygen tetrahedrons to form a glass fiber network structure, and Al2O3, CaO and MgO can respectively aggregate and enhance the network structure formed by SiO2 in different ways, thereby improving the elastic modulus of the network structure. Therefore, in the embodiment of the present invention, the sum of the above four components and the ratio of SiO2, Al2O3 to CaO and MgO are further limited. This is beneficial to further enhance the elastic modulus of the glass fiber while ensuring stable glass drawing.
[0040] According to some preferred embodiments, the sum of the mass percentages of CaO and MgO is not less than 18%.
[0041] MgO has a small radius, high charge, and strong polarization ability. Unlike CaO, MgO can accumulate and increase the degree of polymerization of the glass network, thereby improving the elastic modulus of the glass. Furthermore, through the mutual cooperation of MgO and CaO and further limiting the sum of the masses of CaO and MgO, the elastic modulus of the glass fiber can be further enhanced, while the viscosity of the glass can be reduced, crystallization can be reduced, and the process performance of the glass fiber can be enhanced.
[0042] According to some preferred embodiments, the mass percentage of FeO is 10-18% (for example, it may be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17% or 18%).
[0043] The experiment of the present invention proves that the appropriate content of FeO can ensure that the glass fiber has good drawing performance. If the content of FeO is too low or too high, the glass will be prone to phase separation, which is not conducive to ensuring that the glass fiber has good drawing performance.
[0044] According to some preferred embodiments, the raw materials include the following components, by mass percentage: SiO2: 42-47% (for example, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5% or 47%), Al2O3: 13-16% (for example, 13%, 13.5%, 14%, 14.5%, 15%), , 15.5% or 16%), MgO: 8.5-12% (for example, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5% or 12%), CaO: 10-12.5% (for example, 10%, 11%, 11.5%, 12% or 12.5%), FeO: 9.5-17% (for example, 9.5%, 10%, 10.5%, 11%, 11.5% or 12%). %, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5% or 17%), MnO: 0.2-0.4% (for example, 0.2%, 0.25%, 0.3%, 0.35% or 0.4%), TiO2: 1-7% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 3 .5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5% or 7%), P2O5: 0.1~0.4% (for example, it can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35% or 0.4%), Cr2O3: 0.1~0.35% (for example, it can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3% or 0.35%).
[0045] In the embodiment of the present invention, by further optimizing and limiting each raw material component, it is beneficial for each component to fully play its role, thereby facilitating the increase of the difference between the molding temperature of the fiber and the liquidus temperature of the glass, that is, increasing the drawing window, thereby making the drawing process more stable and being able to maximize the elastic modulus of the glass fiber.
[0046] The present invention also provides a method for preparing the imitation mare basalt glass fiber described in any one of the above items, the preparation method comprising the following steps:
[0047] (1) Conducting phase analysis on lunar soil samples collected from several regions to determine the composition of the lunar soil samples;
[0048] (2) According to the components of the lunar soil samples, the composition of basalt glass fiber was determined and the content of each component was optimized to obtain the raw materials of lunar mare basalt glass fiber;
[0049] (3) melting the raw materials of the imitation mare basalt glass fiber to obtain homogeneous glass;
[0050] (4) Drawing the homogenous glass to obtain the imitation mare basalt glass fiber.
[0051] In an embodiment of the present invention, lunar rocks from different regions of the moon are collected and phase analysis is performed to determine component data of lunar rocks from different regions. Then, based on the component data of the lunar rocks, chemical raw materials are used to physically simulate the lunar rock components, and the components are used as the constituent raw materials of basalt glass fiber. Furthermore, based on the content distribution of the lunar rock components and the elastic modulus and process performance requirements of the glass fiber, the content of each component raw material is optimized and regulated to obtain the constituent raw materials of basalt glass fiber. The raw materials are melted into a glassy state and then quenched with water, and then added to a platinum crucible for drawing. The melt rheological properties of different components are systematically explored under low gravity conditions, thereby preparing imitation lunar sea basalt fibers.
[0052] According to some preferred embodiments, the diameter of the simulated mare basalt glass fiber is 8 to 22 μm, and the elastic modulus is greater than 90 GPa.
[0053] In the embodiment of the present invention, by comprehensively regulating the content of each component raw material, the components can interact with each other, so that stable drawing of 8-22 μm fibers can be achieved in a low-gravity environment, and the elastic modulus of the prepared fibers is as high as 90 GPa or more. At the same time, the embodiment of the present invention improves the fiber forming process performance, reduces the production difficulty, and can adapt to industrial continuous production.
[0054] It should be noted that, in the embodiments of the present invention, when melting, full oxygen combustion, full electric melting or a combination of heat and electricity can be used for kiln melting to form homogeneous glass. Furthermore, the kiln for melting glass can be a melting furnace composed of refractory materials that are resistant to high temperatures and erosion by glass liquid, such as electric fused high zirconium bricks, dense zirconium bricks, electric fused mullite bricks, etc. At the same time, a platinum-substituting furnace constructed of refractory dense zirconium bricks, corundum bricks, electric fused chromium zirconium corundum bricks, and mullite can be used for secondary wire drawing production, that is, first using the high-performance glass fiber composition of the present invention to melt glass, and then using glass to draw glass fibers, or using the kiln passage constructed of the above-mentioned refractory materials for one-step wire drawing production.
[0055] The melting temperature and fiber forming temperature of the imitation lunar mare basalt glass fiber composition in the embodiment of the present invention are relatively high, and a melting furnace and a platinum-substituting furnace or a one-step tank furnace constructed of refractory materials that are resistant to high temperatures and erosion by molten glass are required for glass melting and fiber preparation.
[0056] The embodiment of the present invention further provides a use of any of the above-mentioned imitation mare basalt glass fibers in a composite material reinforcement.
[0057] The imitation lunar basalt glass fiber prepared in the embodiment of the present invention can be used for composite material reinforcement. For example, continuous basalt fiber is used to replace steel bars in the construction industry, bridge industry, and concrete components, which can not only improve the mechanical properties, ductility, and high temperature resistance of the structure, but also solve the problem that traditional concrete steel bars are not resistant to corrosion.
[0058] In order to more clearly illustrate the technical solution and advantages of the present invention, a mare imitating basalt glass fiber and a preparation method thereof are described in detail through several embodiments below.
[0059] According to the raw material composition of each formula listed in Table 1, the required mass percentage of various raw materials in Examples 1 to 13 and Comparative Examples 1 to 2 is calculated respectively, accurately weighed and evenly mixed to prepare the composition raw materials, pneumatically mixed and transported to the kiln charging port, and fed with an automatic feeder, and melted at about 1600°C in a full electric melting or thermal power combined kiln to obtain a clarified and homogenized glass liquid. The melted glass liquid is prepared into glass balls, and the melted glass balls are remelted at 1550°C, and secondary drawing is performed under a vacuum environment to obtain basalt glass fibers, and the fiber is tested for performance, and the results are shown in Table 1.
[0060] The glass density was tested using GB / T 5432 "Glass Density Determination Buoyancy Method". The liquidus temperature was determined using a gradient crystallization temperature test furnace, with reference to ASTM C829. The sample was placed in a platinum boat and placed in a gradient furnace heated to 1400°C for 2 hours. The sample was taken out to observe the crystallization position and the upper limit of the crystallization temperature was calculated based on the temperature gradient. The high-temperature viscosity was determined using the American BROOKFIELD high-temperature viscometer, with reference to ASTM C965. Specifically, the sample was placed in a platinum crucible and placed in a furnace heated to 1500°C. The rotor was then immersed in the high-temperature glass liquid and kept warm for 1 hour. The high-temperature viscosity of the glass liquid was tested by the torque of the rotor. The elastic modulus was tested using an ultrasonic echo method with a glass block. The propagation rate of elastic waves in a solid sample was measured. According to the propagation theory of elastic waves in solids, the propagation rate of sound waves of different modes in solids is related to the corresponding elastic modulus and density of the material, thereby calculating the elastic modulus of the dielectric material.
[0061] Table 1
[0062]
[0063]
[0064] It can be seen from Table 1 that the basalt glass fibers prepared by using the optimized raw material components and content combinations in Examples 1 to 10 not only have good process performance, but also have a high elastic modulus, all higher than 90 GPa, and the highest even reaches above 96 GPa; in Comparative Examples 1 and 2, when the components in the raw materials exceed the range specified in the present invention, the modulus of the glass fiber will be significantly reduced, the process performance is poor, and the stability of the wire drawing during the production process is poor.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A glass fiber imitating lunar mare basalt, characterized in that: The raw materials for preparing the imitation mare basalt glass fiber are determined based on lunar soil component data; The raw materials include the following components in percentage by mass: SiO2: 42-50%, Al2O3: 12-18%, MgO: 7-12%, CaO: 10-14%, FeO: 8-20%, MnO: 0.05-0.4%, TiO2: 1-8%, P2O5: 0.05-0.5%, Cr2O3: 0.05-0.4%.
2. The basalt glass fiber according to claim 1, characterized in that: In terms of mass percentage, it also includes: Na2O: 0-0.3%, K2O: 0-0.3%.
3. The basalt glass fiber according to claim 1, characterized in that: The sum of the mass percentages of SiO2, Al2O3, CaO and MgO is not less than 75%.
4. The basalt glass fiber according to claim 1, characterized in that: The sum of the mass percentages of CaO and MgO is not less than 18%.
5. The basalt glass fiber according to claim 1, characterized in that: The ratio of the sum of the mass percentages of SiO2 and Al2O3 to the sum of the mass percentages of CaO and MgO is not less than 2.
8.
6. The basalt glass fiber according to claim 1, characterized in that: The mass percentage of FeO is 10-18%.
7. The basalt glass fiber according to claim 1, characterized in that: The raw materials include the following components in percentage by mass: SiO2: 42-47%, Al2O3: 13-16%, MgO: 8.5-12%, CaO: 10-12.5%, FeO: 9.5-17%, MnO: 0.2-0.4%, TiO2: 1-7%, P2O5: 0.1-0.4%, Cr2O3: 0.1-0.35%.
8. A method for preparing the imitation mare basalt glass fiber according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) Conducting phase analysis on lunar soil samples collected from several regions to determine the composition of the lunar soil samples; (2) According to the components of the lunar soil samples, the composition of basalt glass fiber was determined and the content of each component was optimized to obtain the raw materials of lunar mare basalt glass fiber; (3) melting the constituent raw materials of the imitation mare basalt glass fiber to obtain homogeneous glass; (4) Drawing the homogeneous glass to obtain the imitation mare basalt glass fiber.
9. The preparation method according to claim 8, characterized in that: The diameter of the imitation lunar mare basalt glass fiber is 8 to 22 μm, and the elastic modulus is greater than 90 GPa.
10. Use of the imitation mare basalt glass fiber according to any one of claims 1 to 7 in a composite material reinforcement.
Citation Information
Cited By
Lunar soil imitating fiber with electromagnetic shielding function
CN121377552A